Elaboración de módulos iconográficos de las vasijas de la cultura panzaleo para aplicarlo en diseños textiles en el periodo 2013 - 2014 - Lema Changoluisa, Héctor Adrian (2016)
The Panzaleo culture crossed the Ecuadorian Highland settled it in different provinces and cities as Latacunga, La Mana, Saquisili and Pujili, leaving signs about their ability to elaborate vessels by researches could access to the vessels collection which are located in the Central Bank Museum of Ecuador now and it will serve to develop this research: "Iconographic Modules developing at Panzaleo Vessels Culture for applying them in textile designs, during 2013-2014”.…